Análisis de la Red de Servicios del Data Center de la CNT.EP Quito y Guayaquil - Cabezas Chora, Oswaldo Raul (2021)
This document deals with a case study on the analysis of the service network of the CNT.EP Quito and Guayaquil data center. Where a central role is spoken in the digital transformation of our country, it is ready to act as its strategic ally that guarantees the user an optimal infrastructure that allows operating and providing in a sustainable, safe, reliable, sustainable, efficient and effective way. Because they help to optimize resources in an agile way, this will reduce the time of adequate attention. It has the international certifications that support its operation in the design and construction of the TIER III data center and LEED certifications (Leadership in Energy and Environmental Design). It is based on the NEC 2001 standards ASCE 7-10 and ACI 318-08 can withstand telluric movements of 8.5 degrees on a richter scale. Its network and interconnection is through fiber optic DWDM and IP MPLS networks. They provide high levels of physical redundancy, complete logic essential to ensure continuity of 99.982%. The technological development refers to the Iass (infrastructure as a service) of Cloud Computing, where the client may have an offer such as security (Firewalls) and a list of application for virtual services. They ensure complete and comprehensive protection to the client's physical and virtual servers to help the business network in order to provide greater protection and security, allowing the client to save on CAPEX (Capital Expenditure) and OPEX (Operating Expenses) optimizing their economy, productivity and availability of support 24 hours a day, 365 days a year.